A Comparative study of machine learning algorithms on thyroid disease prediction - Razia, Shaik; SwathiPrathyusha, P; Vamsi Krishna, N; Sathya Sumana, N (International Journal of Engineering and Technology, 2018)
Thyroid illness is a medicinal state that influences the functionality of the thyroid organ that is thyroid gland [1](Guyton, 2011).The indications of thyroid ailment differ basing upon the type. There are four most common varieties: hypothyroidism (low capacity) which is caused due to the insufficiency of the thyroid hormones; hyperthyroidism (high capacity) which is caused due to the existence of the thyroid hormones more than just sufficient, basic variations from the norm, most normally an augmentation of the thyroid organ; and tumors which can be benign or can cause cancer. It is additionally conceivable to have irregular thyroid capacity tests with no clinical side effects [2](Bauer & al, 2013).In this study a comparative thyroid disease diagnosis were performed by using Machine learning techniques that is Support Vector Machine (SVM), Multiple Linear Regression, NaÃ¯ve Bayes, Decision Trees. For this purpose, thyroid disease dataset gathered from the UCI machine learning database was used.
Keywords: SVM; Multiple Linear Regression; NaÃ¯ve Bayes; Decision Trees.